1996
DOI: 10.1289/ehp.96104634
|View full text |Cite
|
Sign up to set email alerts
|

Lipopolysaccharide-induced hepatic injury is enhanced by polychlorinated biphenyls.

Abstract: After intravenous administration of bacterial lipopolysaccharide (LPS) to rats, polymorphonuclear neutrophils (PMNs) rapidly accumulate in the liver, and midzonal hepatic necrosis is prominent by 6 hr. PMNs are required for the development of hepatic injury in rats. Certain polychlorinated biphenyls (PCBs) can activate PMNs, resulting in production of superoxide anion (O2-.) and release of cytolytic factors from granules. This raises the possibility that PCB exposure might enhance PMN-mediated tissue injury, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 43 publications
1
6
0
Order By: Relevance
“…After weaning, Gram-negative bacteria proliferate in large numbers, and the impaired intestinal epithelium leads to the release of endotoxin into the intestinal mucosa and systematic circulation and then accumulates in the liver. 44 Researchers have found that intraperitoneal injection of lipopolysaccharide leads to an increased level of liver m 6 A in chicken 45 and weaned piglets. 21 The decreased intestinal bacterial population may be one of the causes of decreased m 6 A levels in the intestinal mucosa.…”
Section: Discussionmentioning
confidence: 99%
“…After weaning, Gram-negative bacteria proliferate in large numbers, and the impaired intestinal epithelium leads to the release of endotoxin into the intestinal mucosa and systematic circulation and then accumulates in the liver. 44 Researchers have found that intraperitoneal injection of lipopolysaccharide leads to an increased level of liver m 6 A in chicken 45 and weaned piglets. 21 The decreased intestinal bacterial population may be one of the causes of decreased m 6 A levels in the intestinal mucosa.…”
Section: Discussionmentioning
confidence: 99%
“…It is well established that granulocytes are the main source of cells for superoxide production [40,41]. It is also known that activated granulocytes or neutrophils are intimately related to tissue damage, including that of the liver, lung and other organs [42–44].…”
Section: Discussionmentioning
confidence: 99%
“…Episodes of modest inflammation, although benign on their own, are probably commonplace in people and have the ability to augment the toxicities of several xenobiotic agents ( Liu et al, 2000 ; Lu et al, 2011 ). Indeed, it has been suggested that exposure to endogenous LPS due to increased movement of bacteria across a compromised intestinal mucosa contributes to the hepatotoxicity produced by various agent ( Brown et al, 1996 ; Barton et al, 2000 ; Yee et al, 2000 ). Moreover, LPS influences the pharmacokinetics of drugs ( Ma et al, 2011 ) by modulating the activities of both phase I ( Pan et al, 2003 ; Xu et al, 2006 ) and phase II ( Richardson et al, 2006 ; Alkharfy et al, 2008 ) drug-metabolizing enzymes.…”
Section: Introductionmentioning
confidence: 99%